The Introduction of Words to Our Language - Boboyev Yusuf Beknazarovich (Zien Journals, 2022)
This article gives a brief overview of the words that have entered the Uzbek linguistics and the reasons for their introduction.
Keywords: Neologisms; Persian-Tajik; English; popularity of new words.